The Cologne rebubbling study: a reappraisal of 624 rebubblings after Descemet membrane endothelial keratoplasty. Issue 8 (17th August 2020) - Siebelmann, Sebastian; Kolb, Katharina; Scholz, Paula; Matthaei, Mario; Franklin, Jeremy; Händel, Alexander; Schrittenlocher, Silvia; Hayashi, Takahiko; Guell, Jose L; Bachmann, Björn; Cursiefen, Claus
Abstract : Background/Aims: To analyse graft detachments prior to rebubbling, the influence of rebubbling on the postoperative outcome after Descemet membrane endothelial keratoplasty (DMEK) and the need for rebubbling on the contralateral eye. Methods: In this retrospective cohort study, out of 1541 DMEKs, optical coherence tomography scans and clinical records of 499 eyes undergoing rebubbling after DMEK at the University Hospital of Cologne, Cologne, Germany, were examined. Main Outcome measures were (a) number, localisation and size of graft detachments; (b) influence of rebubbling/s on postoperative outcome after 12 months; and (c) rebubbling risk of the contralateral eye after DMEK. Results: Mean number of detachment areas was 2.02±0.9. Mean lateral diameter of all detachments was 4534.76±1920.83 μm. Mean axial diameter was 382.53±282.02 μm. Detachments were equally distributed over all regions of the cornea. Best spectacle corrected visual acuity ( BSCVA) after 12 months was 0.197±0.23 logarithm of the minimum angle of resolution, endothelial cell density (ECD) was 1575.21± 397.71 cells/mm 2 and mean central corneal thickness (CCT) was 566.37± 68.11 μm. BSCVA, CCT, ECD or endothelial cell loss of all rebubbled patients were not influenced by the number of rebubblings or the time between DMEK and rebubbling. Of the rebubbled patients, which received a DMEK subsequently on the other eye, 193 (58.8%) also received a rebubbling, which was significantly higher, when compared to the overall rebubbling rate of 32.3% (p=0.000). Conclusions: The overall number of rebubblings has no influence on the postoperative outcome after DMEK, if a rebubbling becomes necessary. Patients who received a rebubbling on one eye have an elevated risk for a rebubbling on the fellow eye.